2012
DOI: 10.1103/physrevc.85.064613
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of Ne isotopes in the region of the island of inversion

Abstract: The deformation of Ne isotopes in the island-of-inversion region is determined by the doublefolding model with the Melbourne g-matrix and the density calculated by the antisymmetrized molecular dynamics (AMD). The double-folding model reproduces, with no adjustable parameter, the measured reaction cross sections for the scattering of 28−32 Ne from 12 C at 240MeV/nucleon. The quadrupole deformation thus determined is around 0.4 in the island-of-inversion region and 31 Ne is a halo nuclei with large deformation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
160
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(172 citation statements)
references
References 109 publications
(227 reference statements)
11
160
1
Order By: Relevance
“…[3,4], the DFM was applied to the analysis of σ R for the scattering of Ne isotopes on 12 C at 240 MeV/nucleon as shown in Fig. 1 (b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[3,4], the DFM was applied to the analysis of σ R for the scattering of Ne isotopes on 12 C at 240 MeV/nucleon as shown in Fig. 1 (b).…”
Section: Resultsmentioning
confidence: 99%
“…Although this approximation makes the double-folding potential spherical, it is quite good as shown in Ref. [4].…”
Section: Theoretical Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…Owing to the very systematic and precise measurements of σ I and σ R at RIBF and also extensive theoretical studies, it is indicated that the cross section measurements can be considered not only as the tool to study the halo structures, but also the strong method to probe the gradual development of deformed structures in nuclei as a function of mass number from stable to the drip-line region [3][4][5][7][8][9][10]. In the present study, σ I of fluorine isotopes have been measured systematically from the stable nucleus 19 F to neutron-rich 27 F, the nucleus in the vicinity of the island-of-inversion region.…”
Section: Introductionmentioning
confidence: 99%